2022
DOI: 10.1111/php.13720
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitchable Phosphonate–Fullerene Hybrids with Cholinesterase Activity

Abstract: Modern progress in photopharmocology calls for new generation of compounds joining bioactivity, photoswitchable properties and high selectivity of response to light wavelength. Introduced here, phosphonate–fullerene hybrids are the first representatives of such compounds. Phosphonate–fullerene hybrids were synthesized on a base of fullerene C60 and organophosphates with the function of photoswitchable cholinesterase activity—phosphorylated thiazolotriazole and aminomalonate compounds and studied with FTIR, UV–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…That is why photoactive phosphonates open the path to a new strategy for the treatment of these diseases based on a photopharmacological approach. Our further experiments demonstrated that fullerene@phosphonate hybrids not only retained their biological activity and photoactivation ability under the action of a laser, but also showed an increase in the inhibition difference in diverse conformational states [15].…”
Section: Introductionmentioning
confidence: 62%
“…That is why photoactive phosphonates open the path to a new strategy for the treatment of these diseases based on a photopharmacological approach. Our further experiments demonstrated that fullerene@phosphonate hybrids not only retained their biological activity and photoactivation ability under the action of a laser, but also showed an increase in the inhibition difference in diverse conformational states [15].…”
Section: Introductionmentioning
confidence: 62%
“…Another strategy for the design of photoswitchable cholinesterase inhibitors can be based on the development of compounds demonstrating simultaneously two functions – photoswitching and bioactivity. It should be noting that nowadays there are only a few publications applying this approach [34–38] . Biscussi et.…”
Section: Introductionmentioning
confidence: 99%
“…The novelty of our approach is the synthesis of new compounds having both photoswitchable and bioactive properties without modification/azologization of known pharmacophores. We have previously reported on the synthesis of a series of phosphorylated arylamynomalonates and thiazolotriazol compounds with strong changes in butyrylcholinesterase (BChE) inhibition after laser stimuli [36–38] . Molecular modeling of these compounds showed an interaction with BChE enzyme centers for both isomeric states (before and after laser irradiation).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations